The propaganda World in the prose of the first half of the 1950s. Persuasivestrategies, conventions, language stereotypes - Sałdecka, Karolina (Journal of Education Culture and Society, 2020)
The world depicted in selected novels of the first half of the 1950s functions as a “semantic effect”, precisely shaped by the propaganda of that period. This world is created by narration in order to present the fulfillment of production goals. As a result, we deal with a new reality in which the characters are portrayed first and foremost as manufacturers. Feelings and emotions and their importance are replaced by labor. New civic and social patterns imposed in the novels are to prove that the socialist system is absolutely positive. In order to obtain this goal, primarily lexemes and language constructions are employed, consolidated and repeated in the texts; language conventions that guarantee the coherence of the model of the propaganda-created world. The world presented in the novels set outside Szczecin is narrowed to merely a few thematic fields that are worth discussing.